PEMANFAATAN PUPUK KANDANG UNTUK BUDIDAYA SAWI (Brassica juncea L.) DI TANAH TUKUNGAN - Tuti Heiriyani; Riza Adrianoor Saputra; Helwenda Helwenda (Universitas Lambung Mangkurat, 2022)
One of the efforts to increase mustard production on suboptimal lands such as tidal land with tukungan technology is to offer organic fertilizer. Chicken manure and cow manure can be alternative solutions to improve soil fertility and reduce dependence on the use of inorganic fertilizers in mustard green cultivation. The purpose of this is to determine the ability of organic fertilizers, inorganic fertilizers in increasing soil pH, and the yield of mustard green in tukungan soil. This research was conducted in August to September 2020, at the Greenhouse, Production Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, and the Laboratory of Soil and Water Chemistry, Indonesian Swampland Agriculture Research Institute (Balittra), South Kalimantan. The research method used was a one-factor Completely Randomized Design (CRD) with the treatment of j0 (recommended NPK inorganic fertilizer 250 kg ha-1), j1 (chicken manure 10 ton ha-1), j2 (cow manure 10 ton ha-1), and j3 (combination of chicken manure 5 ton ha-1 and cow manure 5 ton ha-1). The results showed that the application of organic fertilizer of chicken manure 10 ton ha-1 (j1) was able to increase the pH of the tukungan soil by 29%, increase in height of mustard green by 34%, and wet weight of mustard green by 9% compared to the recommended inorganic NPK fertilizer of 250 kg ha-1.